Perempuan dan Politik di Ranah Minang - Deviani Deviani; Nur Iman Subono (Jurnal Ilmu Sosial Indonesia (JISI), 2022)
Abstract. In the beginning of the establishment of West Sumatra and its regencies or cities, it is never a woman elected as regional head.  Since the regional elections in 2015, three women successfully contested the major elections, deputy major, and regent.  The matrilineal system adopted by the people of West Sumatra, placing women in a central position, but cannot encourage women to be present as regional head. Through the qualitative research methods, this study tries to analyze what factors are the causes of women's insecurity as regional heads in West Sumatra.  Then, by using the theory of political recruitment and the glass ceiling, the author finds the factors that women are not elected as regional heads due to the lack of commitment of political parties in West Sumatra in empowering female legislative candidates, in most of the people of West Sumatra, the patriarchal paradigm is still deeply rooted, traditional/cultural system, track record and strong money politics during  the campaign period.Keywords: Women and minang politics, elections, matrilineal.  Abstrak. Dari awal berdirinya Sumatera Barat beserta kabupaten/kotanya, belum pernah satupun perempuan yang terpilih sebagai kepala daerah dan sejak pelaksanaan pilkada langsung yang dilakukan pada tahun 2005 baru ada tiga orang perempuan yang berhasil ikut bertarung dalam pemilihan walikota, wakil walikota dan bupati. Sistem matrilineal yang dianut oleh masyarakat Sumatera Barat, yang menempatkan perempuan pada posisi sentral pun tidak dapat mendorong perempuan untuk hadir sebagai kepala daerah di sana. Dengan metode penelitian kualitatif, penelitian ini mencoba untuk menganalisis mengenai faktor-faktor apa saja yang menjadi penyebab ketidakterpilihan perempuan sebagai kepala daerah di Sumatera Barat. Menggunakan teori rekrutmen politik dan glass ceiling, penulis menemukan faktor-faktor ketidakterpilihan perempuan sebagai kepala daerah karena masih kurangnya komitmen partai politik di Sumatera Barat dalam melakukan pemberdayaan perempuan dalam hal ini melakukan perekrutan terhadap calon-calon perempuan, di sebagian besar masyarakat Sumatera Barat paradigma patriarki masih mengakar kuat, sistem adat/budaya, track record dan masih kuatnya politik uang pada saat kampanye.Kata Kunci: Perempuan Minang dan politik, pilkada, matrilineal.